Plantar vein thrombosis: an uncommon cause of plantar foot pain - Ramos, Marianne Ariely Andretta; Santana, Taiane Costa; Unser, Vinícius; Amaro, Fernanda Regina Piotto; Roncato, Roberto Simeão; Fornazari, Maria Gabriela (ABCS Health Sciences, 2023)
Introduction: Plantar vein thrombosis is a rare condition that can lead to pain, edema, and walking difficulties. It presents a series of predisposing factors, such as recent surgeries, the use of oral contraceptives, and local trauma, among others. Imaging tests are essential for the right diagnosis, and ultrasonography is the modality of choice. As for treatment, there is no consensus in the literature. Report: Case of a 30-year-old patient who sought emergency medical care complaining of sudden severe pain in the plantar region of her right foot with walking difficulties. On physical examination, hyperalgesia was observed in the plantar region, irradiating to the calf, associated with swelling. Color Doppler imaging identified an acute thrombus in the medial plantar vein. Rivaroxaban was initially prescribed and replaced by acetylsalicylic acid after three months. The treatment was effective, and the patient was discharged after 11 months. Conclusion: Plantar vein thrombosis is a rare condition and has a wide range of differential diagnoses so physicians must maintain a high level of clinical suspicion. To improve diagnosis and treatment, it would be necessary to include plantar veins in the investigation protocols of patients suspected of having Deep Venous Thrombosis, besides additional clinical research for improving treatment.